METODE ORDINARY POINT KRIGING UNTUK MEMPREDIKSI INFLASI DI KABUPATEN/KOTA YANG TIDAK TERSAMPEL - Syifa Fauziah; Deltha Airuzsh Lubis (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
Inflation as a macroeconomic indicator has an important role for the government in planning and evaluating development. Inflation estimations conducted by BPS are still limited in some SHK sample cities. This paper proposes Ordinary Point Kriging method to predict inflation rate in some unobserved cities in Java Island based on inflation value in the surrounding districts. By Ordinary Point Kriging method and Gaussian semivariogram model, the predicting result of inflation value in control location at some cities showed MAPE value of 12,56 percent. Meanwhile, the result of application of kriging method in the unobserved regencies/ cities tends to get simillarity of the inflation value in the adjacent location.